Preserving the Sharpeville play: Survivors’ voices as living archives (OHCHR, 2026)
Each year in Sharpeville, survivors of the 1960 massacre and the families of the victims retell history through song, testimony and theatre. With support from UN Human Rights’ Southern Africa Regional Office, this living archive has been recorded and preserved for future generations.
South Africa